Optimalisasi Perilaku Hidup Bersih dan Sehat (PHBS) melalui Edukasi Kesehatan pada Siswa Sekolah - Jihan Salsabillah; Ezi Triani; Wa Ode Herlina; Arsina Arsina; Wa Sinta (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Clean and Healthy Living Behavior (CHLB) is an important effort to improve students’ health status and prevent health problems in the school environment. Lack of understanding regarding personal hygiene, environmental cleanliness, and healthy living habits may increase the risk of disease among school-age children. This community service activity aimed to improve students’ knowledge regarding Clean and Healthy Living Behavior through health education. The community service used a pre-experimental approach with a one group pretest-posttest design. The activity was conducted in May 2026 at SD Negeri 35 Buton involving 34 elementary school students. Data collection was carried out using a questionnaire consisting of 15 questions related to handwashing habits, personal hygiene, waste disposal behavior, healthy eating patterns, and environmental cleanliness. The results of the pre-test showed that most students still had low knowledge regarding CHLB, with 44.1% categorized as having poor knowledge. After health education was provided through counseling, discussion, and question-and-answer sessions, the post-test results showed an increase in students’ knowledge, where 61.8% of students had good knowledge regarding CHLB. The findings indicate that health education through counseling methods is effective in improving students’ understanding and awareness regarding clean and healthy living behavior. Continuous health education programs are needed to encourage students to implement healthy living behaviors consistently in everyday life and to create a clean, safe, and healthy school environment.